Pemberdayaan Usaha Mikro Konveksi Hijab di Dusun Nglongko Kabupaten Jombang - Wicaksono, Agung Prasetyo Nugroho; Soelistyo, Aris (Universitas Muhammadiyah Gresik, 2025)
Our community service partner is a hijab convection micro business located in Nglongko Hamlet, Kebontemu Village, Peterongan District, Jombang Regency. There are three main problems faced by partners, namely obstacles to business capital, obstacles in implementing budget transparency, and monotonous marketing strategies. The purpose of this service program is to provide assistance in the procurement of raw materials, hold counseling and simulation of excel-based integrated financial reports and the implementation of marketing via social media and marketplaces. The method used in our service is to conduct simulations and practice. It is hoped that with this training, service partners will be able to run their next business ventures well.